Exploring Tourism Business Potential: The Role of Gastronomy in Destination Attraction - Supriyadi, Edouard Aryadi; Azhari, Azril; Widianto, Nur (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
The tourism business not only provides goods and services to meet the needs of tourists, but also plays an important role in the overall implementation of the tourism sector. As a comprehensive sector, tourism promises to increase income and foreign exchange pragmatically, while contributing significantly to people's welfare. The main objective is to understand the role of gastronomy in the decision-making of tourists and analyze its impact on local economic growth. With the growing trend of "culinary tourism," this research will provide insight into how tourism destinations can develop business strategies that focus on culinary experiences to increase tourist visits. The results of the study obtained 5 marketing mixes that can become gastronomic tourism attractions.